PENGARUH KUALITAS LAYANAN, CITRA PERUSAHAAN DAN KEPERCAYAAN PADA LOYALITAS KONSUMEN - MARIS AGUNG TRIANDEWO; YUSTINE YUSTINE (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study aims to test the factors that influence loyalty. This research was conducted by collecting 150 data as samples that would represent the population. Data collection is aimed at BCA customers in Jakarta who have used BCA services for at least 1 year. Based on the results of research that has been done there is a positive influence of trust on loyalty, there is a positive influence on service quality on trust, there is a positive influence on service quality on company image, however, there is no positive influence on service quality and company image on loyalty.